(untitled) (Research, Society and Development, 2022)
Aim: Worldwide, neurofunctional physiotherapy has advanced in the purpose of providing new devices in patient’s rehabilitation process with neuro-musculoskeletal disorders and disabilities. Nowadays, rehabilitation is enhanced by the implementation of robotics, electronics and wearable devices which leads physical therapy treatment to a new level. This narrative review addresses smart devices subject by discussing its application in benefited population, categorizing them and exploring its applicability in physiotherapy. Methods: English and portuguese articles from database Pubmed, Scielo, Bireme, ResearchGate and others sources published in the last 10 years were compiled and posteriorly compared and analyzed to determine its relevance and finally included after criterious revision. Results: A total of 53 articles about smart devices were qualitatively analyzed and the information synthesized. This narrative revision shows that this technology is gaining space on physical therapy rehabilitation process , besides it can be used in many parts of the human body, as well as of the changes in user’s quality of living. Conclusion: Despite of its limitations and the lack of availability in poorest people, we believe that these devices are a promising options in the field of health care. Its implementation in clinical-hospital spectrum and availability demands interdisciplinary discussion among different health categories for a better delivery of care for those with neuro-musculoskeletal conditions.